Induction of cardiac fibulin-4 protects against pressure overload-induced cardiac hypertrophy and heart failure - E. D. van Deel; M. Snelders; N. van Vliet; L. te Riet; T. P. P. van den Bosch; L. R. Fiedler; A. C. C. van Spreeuwel; N. A. M. Bax; N. Boontje; C. M. Halabi; T. Sasaki; D. P. Reinhardt; et al. (Communications Biology)
Abstract The prevailing view of fibulin-4 deficient mice is that the cardiac phenotype is the result of aortic and/or valvular disease. In the present study, we have tested whether the cardiac phenotype is, at least in part, the consequence of primary cardiac effects of fibulin-4. We have found fibulin-4 expression to be activated throughout the myocardium in wildtype (fibulin-4+/+) C57Bl/6J;129 Sv mice subjected to transverse aortic constriction (TAC). In contrast, haploinsufficient fibulin-4+/R mice exposed to severe TAC do not show this increase in myocardial fibulin-4 expression, but display altered physical properties of myocardial tissue. Moreover, TAC-induced cardiac fibrosis, pulmonary congestion, and mortality are aggravated in fibulin-4+/R mice. In vitro investigations of myocardial tissue show that fibulin-4 deficiency results in cardiomyocyte hypertrophy, and a decreased beating frequency and contractile force. In conclusion, we demonstrate functions for fibulin-4 in cardiac homeostasis and show that reduced fibulin-4 expression drives myocardial disease in response to cardiac pressure overload, independent of aortic valvular pathology.